2012
DOI: 10.1186/1477-7827-10-89
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic capacity of the placenta as a supplemental source of progesterone during pregnancy in domestic cats

Abstract: BackgroundUntil recently, the corpus luteum (CL) was considered to be the main source of progesterone (P4) during pregnancy in the domestic cat (Felis catus). However, other possible sources of P4 have not been ruled out. Although feline placental homogenates were found to be capable of synthesizing P4, expression of the respective steroidogenic enzymes has not been investigated at the molecular level. Therefore, in the present study, expression of the two major factors involved in the synthesis of P4 - 3beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
3
24
1
2
Order By: Relevance
“…Recent studies confirm that in pregnant queens, the placenta is an additional source of P 4 . Therefore, it should be considered as an important endocrine organ supporting feline pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies confirm that in pregnant queens, the placenta is an additional source of P 4 . Therefore, it should be considered as an important endocrine organ supporting feline pregnancy [7].…”
Section: Introductionmentioning
confidence: 99%
“…After each qPCR reaction, melting curves were obtained by stepwise increases in temperature from 60 to 95°C to ensure single product amplification. Cyclophilin A was previously validated and selected among several different genes as a reference gene (Siemieniuch et al 2012. Quantification of qPCR results was performed by normalising the signals of target genes with the CYC signal using the real-time PCR Miner method, whereby calculation of reaction efficiency and the fractional cycle number at threshold (CT) were based on kinetics of individual qPCR reactions (Zhao & Fernald 2005).…”
Section: Quantification Of Qpcr Results Using the Real-time Pcr Minermentioning
confidence: 99%
“…This, however, does not rule out an intraluteal source of PGF 2α . In cats and lynxes, the prepartal PGFM elevation is accompanied by a decline in plasma P4 (Siemieniuch et al 2012, Painer et al 2014b, indicative of functional luteal regression; however, no complete structural regression, as suggested for the cat (Dawson 1946, Amelkina et al 2015a, is observed in lynxes (Painer et al 2014b). A smaller increase in plasma PGFM, concomitant with a P4 decrease, was shown in prooestrous lynxes (Painer et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations